2002
DOI: 10.2343/geochemj.36.31
|View full text |Cite
|
Sign up to set email alerts
|

Detection of mono- and bicyclic alkanes and their characteristics in Neogene sediments of the Shinjo basin, Japan.

Abstract: Forty five mono-and 12 bicyclic alkanes were detected in a sedimentary sequence from Miocene to Pliocene in the Shinjo basin, northeastern Japan. The monocyclic alkanes included polyalkylcyclohexanes (C 9 , C 10 , C 11 , and C 13 ), a series of n-alkylcyclohexanes (C 9 -C 26 ) and a series of n-alkylcyclopentanes (C 12 -C 26 ). The bicyclic alkanes were from C 9 to C 12 , including cis-and trans-hydrindanes, cis-and transdecalins, and methyl-and dimethyldecalins. These cyclic alkanes were detected at a level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In this study, we analyzed for mono-and bicyclic alkanes, and diamondoid hydrocarbons (adamantanes and diamantanes) in the K/T boundary sediments at Kawaruppu, using the analytical technique which was employed in our study of the Neogene sediments (Yabuta et al, 2002). Here we report the results of the analyses and describe characteristic distributions of these cyclic alkanes above, within and below the boundary claystone in relation to the extinction event.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we analyzed for mono-and bicyclic alkanes, and diamondoid hydrocarbons (adamantanes and diamantanes) in the K/T boundary sediments at Kawaruppu, using the analytical technique which was employed in our study of the Neogene sediments (Yabuta et al, 2002). Here we report the results of the analyses and describe characteristic distributions of these cyclic alkanes above, within and below the boundary claystone in relation to the extinction event.…”
Section: Introductionmentioning
confidence: 99%
“…The oils of X5 and X6 exhibited different values for the 2,6 diethylheptane-to-1,1,3-trimethylcyclohexane ratio, making them distinctive from other samples. This separation could be attributable to the effect of thermal maturity on the composition of branched and cyclic compounds in these two wells (Yabuta et al, 2002), as seen in Fig. 6.…”
Section: Lateral Continuity Of the Asmari Reservoirmentioning
confidence: 91%
“…The 1,1,2,3-TeMCHx was detected in the products of hydrogenated turpentine (Wang, 2011;Zhang et al, 2011a), suggesting it could be derived from the terpenoids of higher plants. Also, it can be derived from the breakdown of carotenoids (Yabuta et al, 2002), which have been reported in both lacustrine and deep marine sediments (Tibbetts, 1980;Zullig, 1982). The similarity in carbon skeletons of these hydrocarbons in oils and monoterpenoids in natural products indicate that the latter might act as precursors during diagenesis or early catagenesis when they are buried in sediments.…”
Section: Origin Of Monoterpenoid Hydrocarbons In Oils and Condensatesmentioning
confidence: 97%
“…Göhring et al (1967) isolated a series of 2,6-dimethylalkanes including 2,6-DMO from Nigerian Cretaceous source rock extracts and oils and suggested squalene and/or carotenoids as the precursors of these carbon skeletons. Yabuta et al (2002) detected 1-methyl-4-isopropylcyclohexane (1-M-4-iPCHx) and 1,1,2, 3-tetramethylcyclohexane (1,1,2,3-TeMCHx) from Miocene to Pliocene sediments in the Shinjo Basin, NE Japan. While 1,1,2,3-TeMCHx can be derived from breakdown of carotenoids (Yabuta et al, 2002), it can also be derived from terpenoids as has been detected in the products of hydrogenated turpentine (Zhang et al, 2010a;Wang, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation